CTGF siRNA ameliorates tubular cell apoptosis and tubulointerstitial fibrosis in obstructed mouse kidneys in a Sirt1-independent manner - Ren Y; Du C; Yan L; Wei J; Wu H; Shi Y; Duan H (Dove Medical Press, 2015)
Yunzhuo Ren,* Chunyang Du,* Li Yan, Jingying Wei, Haijiang Wu, Yonghong Shi, Huijun Duan Department of Pathology, Hebei Medical University, Shijiazhuang, Hebei, People’s Republic of China *These authors contributed equally to this work Abstract: Transforming growth factor-β1 (TGF-β1) plays an important role in the pathogenesis and progression of chronic kidney disease. Connective tissue growth factor (CTGF) is a critical fibrogenic mediator of TGF-β1. Mammalian sirtuin 1 (Sirt1) is reported to attenuate renal fibrosis by inhibiting the TGF-β1 pathway. This study was designed to detect whether the delivery of CTGF siRNA in vivo directly ameliorates renal fibrosis. Furthermore, the relationship with Sirt1 underlying the protective effect of CTGF siRNA on interstitial fibrosis and apoptosis was explored. Here, we report that the expressions of CTGF and TGF-β1 were increased while Sirt1 expression and activity were both dramatically decreased in mouse kidneys with unilateral ureteral obstruction. Recombinant human TGF-β1 treatment in HK-2 cells increased CTGF levels and remarkably decreased Sirt1 levels and was accompanied by apoptosis and release of fibrosis-related factors. Recombinant human CTGF stimulation also directly induced apoptosis and fibrosis. The CTGF siRNA plasmid ameliorated tubular cell apoptosis and tubulointerstitial fibrosis, but did not affect Sirt1 expression and activity both in vivo and in vitro. Furthermore, overexpression of Sirt1 abolished TGF-β1-induced cell apoptosis and fibrosis, while Sirt1 overexpression suppressed CTGF expression via stimulation by TGF-β1. This study provides evidence that treatment strategies involving the delivery of siRNA targeting potentially therapeutic transgenes may be efficacious. Our results suggest that the decrease in Sirt1 is associated with the upregulated expression of CTGF in renal fibrosis, and may aid in the design of new therapies for the prevention of renal fibrosis. Keywords: ureteral obstruction, Sirt1, CTGF, fibrosis, apoptosis